Sistem Keamanan Penerimaan Paket Menggunakan Face Recognition dan Metode Comparison Algorithms dengan Rasberry Pi Berbasis Internet of Things - Azmi, Frisca Nurul; Z, Tjut Awaliyah; Suriansyah, M Iqbal (LPPM STIKI MALANG, 2024)
In this research will use a Raspberry Pi for face processing. Raspberry Pi was chosen because the facial recognition process requires larger CPU processing. Then for input, use a webcam. Then it will be processed by the Raspberry Pi which will then open the door lock and the package can be taken by the buyer. Research Objective